Ferroptosis and Its Multifaceted Roles in Cerebral Stroke - Zhang, Yongfa; Lu, Xiaoyang; Tai, Bai; Li, Weijia; Li, Tao (Frontiers in Cellular Neuroscience, 2021)
Ferroptosis is a unique regulated cell death defined by the intracellular iron overload and distinct biological features compared with other well-known programmed cell death. Ferroptosis can be triggered by many causes including decreased expression of Glutathione (GSH), inhibition of the function of glutathione-dependent peroxidase 4 (GPX4) and system xc-, all of which finally lead to the over-accumulation of lipid peroxides in the cell. Ferroptosis has been reported to play an important role in the pathophysiological process of various cancers. In recent years, much evidence also proved that ferroptosis is involved in the progress of cerebral stroke. In this review, we summarized the characteristics of ferroptosis and the potential relationship between ferroptosis and ischemic and hemorrhagic stroke, to provide new targets and ideas for the therapy of stroke.